Constitutional protection of environment in a social market economy - Álvarez Miranda, Ernesto (2016)
In this paper develops the fields of social market economy regarding the constitutional protection of the healthy and balanced environment. It also raises the challenges of public and private investment in relation to extractive industries located in Peru.